2019
DOI: 10.1111/hex.12872
|View full text |Cite
|
Sign up to set email alerts
|

Media content analysis of the introduction of a “soft opt‐out” system of organ donation in Wales 2015‐17

Abstract: In an attempt to improve organ donation rates, some countries are considering moving from “opt‐in” systems where citizens must express their willingness to be an organ donor, to “opt‐out” systems where consent is presumed unless individuals have expressed their wishes otherwise, by, for example, joining an “opt‐out” register. In Wales—a part of the United Kingdom—the devolved government recently legislated for an “opt‐out” system. For the change to be effective, a public awareness campaign was critical to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
(41 reference statements)
0
10
1
Order By: Relevance
“…The majority of coverage by news media in relation to both organ donation and the change in the law was positive, especially when adjusted for the annual number of views, with little change during the period of analysis. This differs from the tone towards the Welsh opt-out policy observed in a similar analysis carried out in 2015–2017 which found that the tone of coverage became more supportive of the Welsh policy over time ( 12 ). This difference may be explained, at least in part, by changes in attitudes towards the ‘soft opt-out' law during the intervening period.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The majority of coverage by news media in relation to both organ donation and the change in the law was positive, especially when adjusted for the annual number of views, with little change during the period of analysis. This differs from the tone towards the Welsh opt-out policy observed in a similar analysis carried out in 2015–2017 which found that the tone of coverage became more supportive of the Welsh policy over time ( 12 ). This difference may be explained, at least in part, by changes in attitudes towards the ‘soft opt-out' law during the intervening period.…”
Section: Discussioncontrasting
confidence: 87%
“…Implementing population health policy changes such as this are complex and often rely heavily on public media communications and carefully crafted messages delivered through multiple channels ( 11 ). When Wales (a devolved country within the UK) switched to a very similar system, media tone towards organ donation and the new policy changed—becoming more positive after implementation over time ( 12 ). Previous research has demonstrated that the topic of organ donation is newsworthy but when linked with controversial narratives will be given more prominence (e.g., front page headlines) ( 13 ) and that, as well as playing an important role in communicating information about organ donation, local and national media can both reflect and influence public opinion ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…This was a view supported by patient and public representatives who co-produced the current study. In a separate analysis of media coverage,16 we found a change to a more positive and supportive tone after 1 December 2015 when the soft opt-out was fully implemented that aligns with a general trend in improvements to consent rates.…”
Section: Discussionmentioning
confidence: 67%
“…Negative media coverage had a damaging effect on trust in NHSBT 54 . There was subsequent appetite for an inquiry that considered all nations within the United Kingdom, as well as an expanded mandate to assess evidence of a government cover‐up 55 .…”
Section: The Penrose Inquirymentioning
confidence: 99%